Inovasi Pemberdayaan Industri Kreatif Nasional sebagai Upaya Pemulihan Perekonomian Nasional Ditinjau Berdasarkan Konsep Pentahelix - Medlimo, Rodrikson Alpian (Maliyah : Jurnal Hukum Bisnis Islam, 2022)
This study explains the pentahelix concept as a government synergy with various actors in developing innovations to empower the national creative industry to be an essential thing to implement massively in Indonesia, especially after the Covid-19 pandemic hit. The recovery of the national economy based on the pentahelix concept is a reference for the government's seriousness in alleviating the problem of social inequality. The increasing number of gaps during the Covid-19 pandemic is a challenge and a reality that the Indonesian people must face. The increase in the number of holes is exacerbated by the condition of the Indonesian people, who need more creativity and innovation, which in turn gives birth to low-quality human resources. Pentahelix terminology must touch holistically and be carried out consistently and continuously as a government work program. Therefore, the involvement of various parties is the key to recovering the national economy, especially after the Covid-19 pandemic.